Clinical Application of Traditional Chinese Medicine in Pneumonia Complicated with Heart Failure based on Data Mining Algorithms - Deng, Qingping; Yang, Rongyuan; Zeng, Xing; Cai, Huayang; Liu, Qing (Current Traditional Medicine, 2025)
ObjectiveThis study aimed to investigate and analyze the existing literature regarding the clinical utilization of Traditional Chinese Medicine (TCM) in cases of pneumonia complicated by heart failure by employing data mining algorithms.MethodsThe study gathered medical cases of treating pneumonia complicated with heart failure from CNKI, Wanfang, VIP, and PubMed databases without imposing any temporal restrictions. We extracted medication details and built a comprehensive database in Microsoft Excel 2019. The analysis included frequency, cluster, and complex network analyses, along with association rule visualization. These analytical procedures were executed using specialized software, such as SPSS Statistics 26.0, SPSS Modeler 18.0, and Gephi.ResultsThis study included 47 articles meeting specific criteria, with 53 prescriptions and 110 different drugs. Pathological patterns observed included heart-yang deficiency, lung obstruction by phlegm-heat, qi-yin deficiency, and internal closure with external prolapse. Medications fell into categories like tonics, antitussives, heat-clearing, and wind-dispersing drugs, with cold, warm, and neutral properties most common. Bitter, sweet, and pungent tastes were predominant. Many drugs were found to target specific meridians like the lung, stomach, spleen, and heart. Cluster analysis grouped 40 frequently used drugs into 6 categories, revealing complex relationships. Network analysis identified core drugs for treating pneumonia complicated with heart failure, emphasizing their importance in managing this complex medical condition.ConclusionKey Chinese herbal medicines for pneumonia complicated with heart failure include Ophiopogon japonicus, liquorice root, red ginseng, Ansu apricot seed, ginseng root, pepperweed seed, and Chinese ephedra herb. They focus on promoting lung Qi, strengthening Qi and blood, and improving blood circulation to address stasis. This data supports future clinical research in managing pneumonia and heart failure.
Keywords: medication patterns